2010
DOI: 10.1177/0091270009347475
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin Ascending Multiple Oral Dosing Phase I Study in Noncirrhotic Patients With Chronic Hepatitis C

Abstract: Silymarin, derived from the milk thistle plant Silybum marianum, is widely used for self-treatment of liver diseases, including hepatitis C virus (HCV), and its antiviral activity has been demonstrated in vitro and in HCV patients administered an intravenous formulation of the major silymarin flavonolignans, silybin A and silybin B. The safety and dose-exposure relationships of higher than customary oral doses of silymarin and its acute effects on serum HCV RNA were evaluated in noncirrhotic HCV patients. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 38 publications
7
138
3
2
Order By: Relevance
“…Chronic inflammation occurs in patients with hepatic damage. Thus, for patients with compensatory cirrhosis, hepatitis C, and non-alcoholic hepatic steatosis, the bioavailability of compounds present in silymarin may be affected, which may also explain the low effectiveness of treatment with flavonoids in these patients [12,13] . Sy-Cordero et al [14] isolated four key flavolignans and diastereoisomers (silybin A, silybin B, isosilybin A, and isosilybin B) from S. marianum on a gram-scale.…”
Section: Overviewmentioning
confidence: 99%
“…Chronic inflammation occurs in patients with hepatic damage. Thus, for patients with compensatory cirrhosis, hepatitis C, and non-alcoholic hepatic steatosis, the bioavailability of compounds present in silymarin may be affected, which may also explain the low effectiveness of treatment with flavonoids in these patients [12,13] . Sy-Cordero et al [14] isolated four key flavolignans and diastereoisomers (silybin A, silybin B, isosilybin A, and isosilybin B) from S. marianum on a gram-scale.…”
Section: Overviewmentioning
confidence: 99%
“…It has been shown that HCV modifies antioxidant defense mechanisms yielding a cellular oxidative imbalance [29,31,41] . Several authors, including our research group, have demonstrated that HCV effectively modifies gene expression regulatory proteins of oxidative stress as SOD and catalase [26,31,33] .…”
Section: Antioxidant Therapymentioning
confidence: 99%
“…As an example a phase Ⅰ trial assessing the efficacy of oral doses of silymarin in non-responders HCV infected patients demonstrated no adverse effects but also showed no antiviral efficacy against HCV [41] . However, in other report the administration of intravenous (iv) silibilin in non-responders HCV infected patients decreased HCV-RNA levels in a dose-dependent manner [58] .…”
Section: Silymarin Complexmentioning
confidence: 99%
“…We have previously reported on the ascending multiple dose pharmacokinetics of silymarin in noncirrhotic patients with chronic HCV infection (Hawke et al, 2010) obtained from a double-blind, placebocontrolled phase 1 trial that was conducted in patients with either HCV or NAFLD. An unexpected finding was that dose proportionality in the pharmacokinetics of parent silymarin flavonolignans was not observed in HCV patients with well compensated liver disease at silymarin doses greater than 560 mg when administered orally every 8 h (Hawke et al, 2010).…”
Section: Introductionmentioning
confidence: 99%